Empowerment Model and Fulfillment of Elderly Rights through Elderly Schools (Review of Law Number 13 of 1998) - Waryatun, Waryatun; Rodiyah, Rodiyah; Utari, Indah Sri (Law Research Review Quarterly, 2023)
The empowerment and fulfillment of senior rights model based on Law Number 13 of 1998 in Tegal District and Central Java Province have begun to fulfill the rights of senior citizens through schools, with support from the community, village government, provincial government, and central government, including support from families with senior members, even though it has not yet been fully synchronized and quickly implemented in each region. Socialization continues to be conveyed to the public about the need for attention and respect for senior citizens by all segments of society, even though there are still societal stigmas that consider senior citizens as having many limitations and being unproductive, and therefore not needing special attention from the government.